Modified 128-EEA2 Algorithm by Using HISEC Lightweight Block Cipher Algorithm with Improving the Security and Cost Factors - Alyaa Ghanim Sulaiman; Sufyan Salim Mahmood AlDabbagh (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
128-EEA2 (Evolved Packet System Encryption Algorithm 2) is a confidentiality algorithm which is used to encrypt and decrypt block of data based on confidentiality key. This confidentiality algorithm 128-EEA2 is based on the AES-128 which is the block cipher algorithm of 128 bit in CTR mode. In this paper, we are going to replace the AES-128 block cipher algorithm by HISEC block cipher algorithm for two reasons such as reducing cost and ameliorate security factor.